2023
DOI: 10.3390/cancers15112976
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Role of Serum Thyroglobulin after Surgery and before Radioactive Iodine Therapy in Patients with Thyroid Carcinoma

Abstract: Introduction: Thyroidectomy followed by radioactive iodine therapy (RAI) is the treatment of choice for differentiated thyroid carcinoma (DTC). Serum thyroglobulin (Tg) measurement has proved to be useful for predicting persistent and/or recurrent disease during follow-up of DTC patients. In our study, we evaluated the risk of disease recurrence in patients with papillary thyroid carcinoma (PTC), who were treated with thyroidectomy and RAI, by measuring serum Tg at different time-points: at least 40 days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Some studies ( 27 , 28 ) showed the important role of serum Tg in predicting node metastasis while the others ( 7 , 29 ) showed that there was weak correlation between Tg and metastatic disease. There is still controversy over whether preoperative serum Tg can predict lymph node metastasis in PTCs.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies ( 27 , 28 ) showed the important role of serum Tg in predicting node metastasis while the others ( 7 , 29 ) showed that there was weak correlation between Tg and metastatic disease. There is still controversy over whether preoperative serum Tg can predict lymph node metastasis in PTCs.…”
Section: Discussionmentioning
confidence: 99%